Rich Dad, S Cashflow Quadrant - Jantaburom, Sudjai; Leeka, Jaras; Komaro, PhraChaiya; Athipanyo, PhraatikarnPramaul (Journal of Graduate MCU KhonKaen Campus, 2023)
This book review aims to present the financial independence of four occupations: employee, and self-employed, business owner, investor, and what are the factors that make people in these 4 professions different in terms of work and finance? People who strive for success must be ready to transform themselves by learning new ways. And ready to move from the industrial age to the information age will give that personal financial freedom.